Pendampingan Pendirian Madrasah Aliyah Nurul Qur’an Kaliwiro Kabupaten Wonosobo - Robingun Suyud El Syam; Ngatoillah Linnaja; Alfan Nurngain; Akhmad Mustangin (Cv. Utility Project Solution, 2021)
Madrasah are one of the pillars of Islamic education since the time of the Seljuq caliphate which gave birth to a golden generation of Islamic scientists, so it is necessary to present this spirit in the form of new madrasah. By complying with the regulations of the Director General of Islamic Education Number 1385 of 2014 concerning Technical Instructions for Establishing Madrasah organized by the community, mentoring new schools by helping the organizers of Madrasah Aliyah Nurul Qur'an Kaliwiro prepare requirements related to new school operational permits, until obtaining permits the operational. With the fulfillment of administrative requirements, technical requirements, eligibility requirements, following the procedures for establishing a madrasah, and understanding the validity period of the operational permit, the operational permit has been successfully established.